Aspects of stone weathering, decay and conservation : proceedings of the 1997 Stone Weathering and Atmospheric Pollution Network Conference (SWAPNET '97), the Robert Gordon University, 15-17 May 1997 - Jones, Melanie S.; Wakefield, Rachael D. (Imperial College Press, 1999)
"This book brings together papers by scientists, conservators and building surveyors active in stone decay and conservation research within the UK. It addresses issues of stone weathering, mechanisms and rates, the effects of urban pollution, cleaning methods, and the role of the conservator within research. The concepts regarding the value of stone heritage are also discussed as an important aspect towards retaining our diverse building heritage."page 4 of cover.